Necroptosis: A new target for prevention of osteoporosis - Hu, Xinli; Wang, Zheng; Kong, Chao; Wang, Yu; Zhu, Weiguo; Wang, Wei; Li, Yongjin; Wang, Wei; Lu, Shibao (Frontiers in Endocrinology, 2022)
Multiple causes may contribute to osteoporosis, characterized by a loss in bone mass and density as a consequence of the degradation of bone microstructure and a resultant rise in bone fragility. Increasing attention has been paid recently to necroptosis's function in the development of osteoporosis. Necroptosis is orchestrated by a set of proteins known as receptor-interacting protein kinase (RIPK)1, RIPK3, and mixed lineage kinase domain-like protein (MLKL). A necrosome is formed by MLKL, RIPK1, RIPK3, and RIPK3-RIPK3. A dissociated MLKL forms pores in the plasma membrane and eventually leads to necroptosis after translocating from the necrosome. In this review, we discuss a detailed understanding of necroptosis and its associated processes, a better understanding of its interactions with osteoclasts, osteoblasts, and osteocytes, and the associations between necroptosis and diabetic osteoporosis, steroid-induced osteoporosis, and postmenopausal osteoporosis. It's important to note that this is the first review paper to consolidate current data on the role of necroptosis in osteoporosis, and it offers fresh hope for the future treatment of this disease.